Exosomes-loaded thermosensitive hydrogels for corneal epithelium and stroma regeneration. (January 2022) - Tang, Qiaomei; Lu, Bing; He, Jian; Chen, Xiao; Fu, Qiuli; Han, Haijie; Luo, Chenqi; Yin, Houfa; Qin, Zhenwei; Lyu, Danni; Zhang, Lifang; Zhou, Min; et al.
Abstract: Corneal damage forms scar tissue and manifests as permanent corneal opacity, which is the main cause of visual impairment caused by corneal diseases. To treat these diseases, herein, we developed a novel approach based on the exosome derived from induced pluripotent stem cell-derived mesenchymal stem cells (iPSC-MSCs) combined with a thermosensitive hydrogel, which reduces scar formation and accelerates the healing process. We found that a thermosensitive chitosan-based hydrogels (CHI hydrogel) sustained-release iPSC-MSC exosomes can effectively promote the repair of damaged corneal epithelium and stromal layer, downregulating mRNA expression coding for the three most enriched collagens (collagen type I alpha 1, collagen type V alpha 1 and collagen type V alpha 2) in corneal stroma and reducing scar formation in vivo . Furthermore, iPSC-MSCs secrete exosomes that contain miR-432-5p, which suppresses translocation-associated membrane protein 2 (TRAM2), a vital modulator of the collagen biosynthesis in the corneal stromal stem cells to avert the deposition of extracellular matrix (ECM). Our findings indicate that iPSC-MSCs secrete miRNA-containing exosomes to promote corneal epithelium and stroma regeneration, and that miR-432-5p can prevent ECM deposition via a mechanism most probably linked to direct repression of its target gene TRAM2. Overall, our exosomes-based thermosensitive CHI hydrogel, is a promising technology for clinical therapy of various corneal diseases.